2021
DOI: 10.3390/app11093906
|View full text |Cite
|
Sign up to set email alerts
|

Classification Performance of Thresholding Methods in the Mahalanobis–Taguchi System

Abstract: The Mahalanobis–Taguchi System (MTS) is a pattern recognition tool employing Mahalanobis Distance (MD) and Taguchi Robust Engineering philosophy to explore and exploit data in multidimensional systems. The MD metric provides a measurement scale to classify classes of samples (Abnormal vs. Normal) and gives an approach to measuring the level of severity between classes. An accurate classification result depends on a threshold value or a cut-off MD value that can effectively separate the two classes. Obtaining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Jin and Chow performed Box-Cox transformation on MD and used three times the standard deviation of the transformed normal distribution to set the threshold and applied it to the motor fault diagnosis of cooling fans [22]. Ramlie et al compared the performance of the four most common thresholding methods, namely, the Type I-Type II error method, the probabilistic thresholding method, the receiver operating characteristics (ROC) curve, and the Box-Cox transformation method, in 20 different datasets and recommended the use of the Type I-Type II error method due to its lower computational complexity [23].…”
Section: Rajesh Et Al Advised That If Other Variable Selection Method...mentioning
confidence: 99%
“…Jin and Chow performed Box-Cox transformation on MD and used three times the standard deviation of the transformed normal distribution to set the threshold and applied it to the motor fault diagnosis of cooling fans [22]. Ramlie et al compared the performance of the four most common thresholding methods, namely, the Type I-Type II error method, the probabilistic thresholding method, the receiver operating characteristics (ROC) curve, and the Box-Cox transformation method, in 20 different datasets and recommended the use of the Type I-Type II error method due to its lower computational complexity [23].…”
Section: Rajesh Et Al Advised That If Other Variable Selection Method...mentioning
confidence: 99%
“…Saad et al [39] developed an MTS-based graphical user interface to analyze and classify normal and abnormal patients under MFlex service for a better monitoring system. Ramlie et al [40] concluded that none of the four thresholding methods outperformed one over the others in (if it is not for all) most of the datasets. Harudin et al [41] proved that incorporating Bitwise Artificial Bee Colony (BitABC) techniques into Taguchi's T-Method methodology effectively improved prediction accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[37] used the MFlex service to make the tracking system better by creating an MTS-based graphical user interface for analyzing and sorting patients into groups of normal and abnormal variants. According to [38], none of the four thresholding approaches outperformed the others in almost all of the datasets. [39] showed that combining Bitwise Artificial Bee Colony (BitABC) methods along with Taguchi's T-Method greatly improved the accuracy of predictions.…”
Section: Introductionmentioning
confidence: 96%